Application Progress of Transcranial Direct Current Stimulation in Rehabilitation of Chronic Low Back Pain - SHI Jian; WAN Ruihan; WANG Yafei; GONG Chen; WANG Yuling (康复学报)
Low back pain (LBP) is one of the common chronic pains in clinical practice, affecting about two-thirds of LBP patients continue to deteriorate into Chronic low back pain (CLBP) after the initial onset. CLBP imposes a significant financial burden on both patients and society. At present, pharmacological treatments remains the primary treatment approach in clinical practice, but its long-term efficacy is limited. Long-term use of analgesics may result in some adverse effects in such patients, including the increased risk of depression and fracture. Notably, patients with CLBP have abnormalities in brain function and structure involved in pain regulation and stimulation of the brain region involved in pain processing may be an effective treatment for them. Transcranial direct current stimulation (tDCS) is a burgeoning non-invasive brain neuromodulation technique, which has the advantages of improved safety and few negative side effects. It applies specific low-intensity current to specific brain areas through electrodes, regulate synaptic plasticity, change cortical excitability, and achieve the regulation of neural activity in the brain, and has shown certain efficacy in the treatment of chronic pain. However, due to the complexity of the pathogenesis of CLBP and the inconsistency of stimulus parameters, the results of clinical studies on tDCS in this disease are quite different. This article reviews the current domestic and international research progress of tDCS in CLBP rehabilitation in recent years and discusses the factors that affect its curative effect (e.g., stimulation target, frequency, and synergistic treatment scheme) and possibly effective treatment modes. Additionally, the paper summarized the potential analgesic mechanism of tDCS in the treatment of CLBP, aiming to provide new ideas for the nonpharmacologic treatment of this disease. The review found that a single session of tDCS or a combination of tDCS and peripheral intervention significantly improved the pain intensity of patients with CLBP, but the effects of multiple sessions of tDCS on CLBP were not significant. Compared with the primary motor cortex, the prefrontal area showed a better therapeutic effect as the stimulating site for tDCS treatment of CLBP. In addition, the mechanism of the effect of tDCS on CLBP may be related to its regulatory effects on pain-related neural signaling pathways, regional cerebral blood flow, and synaptic plasticity. In the future, high-quality clinical studies with multi-center, large samples, long-term follow-up, and comparison of different stimulus parameters of tDCS should be further carried out to explore the therapeutic potential of tDCS to treat patients with CLBP from multiple dimensions and optimize the stimulation protocols of tDCS.